Small extracellular vesicles deliver miR‐21 and miR‐217 as pro‐senescence effectors to endothelial cells. Issue 1 (18th February 2020) - Mensà, Emanuela; Guescini, Michele; Giuliani, Angelica; Bacalini, Maria Giulia; Ramini, Deborah; Corleone, Giacomo; Ferracin, Manuela; Fulgenzi, Gianluca; Graciotti, Laura; Prattichizzo, Francesco; Sorci, Leonardo; Battistelli, Michela; et al.
ABSTRACT: The role of epigenetics in endothelial cell senescence is a cutting‐edge topic in ageing research. However, little is known of the relative contribution to pro‐senescence signal propagation provided by microRNAs shuttled by extracellular vesicles (EVs) released from senescent cells. Analysis of microRNA and DNA methylation profiles in non‐senescent (control) and senescent (SEN) human umbilical vein endothelial cells (HUVECs), and microRNA profiling of their cognate small EVs (sEVs) and large EVs demonstrated that SEN cells released a significantly greater sEV number than control cells. sEVs were enriched in miR‐21‐5p and miR‐217, which target DNMT1 and SIRT1. Treatment of control cells with SEN sEVs induced a miR‐21/miR‐217‐related impairment of DNMT1‐SIRT1 expression, the reduction of proliferation markers, the acquisition of a senescent phenotype and a partial demethylation of the locus encoding for miR‐21. MicroRNA profiling of sEVs from plasma of healthy subjects aged 40–100 years showed an inverse U‐shaped age‐related trend for miR‐21‐5p, consistent with senescence‐associated biomarker profiles. Our findings suggest that miR‐21‐5p/miR‐217 carried by SEN sEVs spread pro‐senescence signals, affecting DNA methylation and cell replication.